Neuropsychological outcome and its correlates in the first year after adult mild traumatic brain injury: A population-based New Zealand study. (6th December 2015) - Barker-Collo, Suzanne; Jones, Kelly; Theadom, Alice; Starkey, Nicola; Dowell, Anthony; McPherson, Kathryn; Ameratunga, Shanthi; Dudley, Margaret; Te Ao, Braden; Feigin, Valery; ,
Abstract: Objective : The relationship between moderate/severe traumatic brain injury (TBI) and cognitive deficits is well known. The nature, duration and predictors of cognitive difficulties post-mild TBI remain unclear. This study examined cognitive, mood and post-concussion outcomes of mild TBI over 1-year post-injury. Method : Adults (>15 years) with mild TBI ( n  = 260) completed neuropsychological (CNS-Vital Signs, Behavioural Dyscontrol Scale), mood (Hospital Anxiety Depression Scale) and behavioural assessments (Cognitive Failures Questionnaire, Rivermead Post-Concussion Questionnaire) at baseline, 1-, 6- and 12-months post-injury. Results : Over the 12-months post-injury self-reported cognition ( p  = 0.027), post-concussion symptoms ( p  < 0.001), depression ( p  < 0.001), anxiety ( p  < 0.001) and dyscontrol ( p  = 0.025) improved significantly. Assessments of memory, processing speed, executive function, psychomotor speed/reaction time, complex attention and flexibility also improved significantly. At baseline >20% of individuals produced very low scores on executive ability, complex attention and cognitive flexibility. At 1- and 6-month follow-ups >20% of participants were very low for complex attention, with 16.3% remaining so at 12-months. Executive abilities and speed were related to post-concussion symptoms, mood and self-reported cognition at 12-months. Conclusions : Whilst significant improvements were noted across measures over time, a significant proportion of individuals still perform poorly on neuropsychological measures 12-months after mild TBI; and these were linked to post-concussion symptoms, mood and self-reported cognitive outcomes. This implies a longer trajectory for recovery than has previously been suggested, which has implications for provision of assessment and rehabilitation services for more extended periods.